Use of Thermo-Modified Wood Massif in Making Parametric Exterior Furniture - R. Shaikhutdinova, A.; R. Safin, R.; V. Nazipova, F.; R. Mukhametzyanov, S. (International Journal of Engineering and Technology, 2018)
This paper proposes the use of an array of heat-treated wood of various species to make parametric furniture for the purpose of operation in the exterior, and on objects in conditions of high humidity. The dependence of change in the color range of thermowoods depending on the temperature and duration of treatment is presented. Experiments were carried out to study the biological stability of thermally modified wood treated by various technologies including: vacuum-convective thermal modification in superheated steam, convective thermal modification in high-pressure saturated steam, as well as in hydrophobic liquids, in flue gas and vacuum-conductive thermal-modifying. The degree of resistance of wood was determined, which allows to conclude that the mass losses of heat-treated specimens caused by the destructive action of fungi are significantly lower compared to untreated ones. The researchwas conducted to determine the numerical characteristics of microroughness of the polished surface of wood, thermally modified at different temperatures.Â Â Â